2011
DOI: 10.1159/000321051
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Treatment

Abstract: Inflammatory mucosal disorders are treated conventionally with potent or superpotent topical corticosteroids. For more than 20 years, topical cyclosporine has been used in the management of oral mucous membrane affections. Recently other topically applied calcineurin inhibitors, namely tacrolimus and pimecrolimus, expanded the armamentarium for the treatment of inflammatory mucosal diseases. This chapter places its main emphasis on the efficacy and safety of topical calcineurin inhibitors in the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Dampening excessive inflammation creates a microenvironment for oral mucositis healing 1316 . The antagonistic effect of Smad7 on both TGF-β and NF-κB signaling 18 could make Smad7 a more efficient anti-inflammatory molecule than other agents targeting only NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dampening excessive inflammation creates a microenvironment for oral mucositis healing 1316 . The antagonistic effect of Smad7 on both TGF-β and NF-κB signaling 18 could make Smad7 a more efficient anti-inflammatory molecule than other agents targeting only NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Two Palifermin clinical trials in head and neck cancer patients showed that Palifermin reduced severe oral mucositis incidence from 67% and 69% to 51% and 54%, respectively 5,6 . Other oral mucositis drugs in clinical trials or pre-clinical studies include growth factors 79 , agents for radioprotection 1012 , anti-inflammatory agents or immune modulators 1316 .…”
mentioning
confidence: 99%
“…The role of TCIs in the treatment of inflammatory mucosal disorders [98], and in particular of LS, has been recently reviewed [99]. The use of TCIs in LS is off label.…”
Section: Treatmentmentioning
confidence: 99%
“…The topical calcineurin inhibitors pimecrolimus and tacrolimus have a significant anti-inflammatory activity, immunomodulatory effects and a low systemic immunosuppressive potential; however, they are off-label and considered dangerous to develop tumours [21,22]. Treatment of LS with topical testosterone was dropped out due to its very limited efficacy and to the noticeable superiority, in terms of clinical results, of corticosteroids [23,24].…”
Section: Introductionmentioning
confidence: 99%